On Henig Regularization of State-Constrained Optimal Control Problem for the p-Laplace Equation - P. I. Kogut (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Modelûvannâ, 2015)
We study a Dirichlet optimal control problem for a quasilinear monotone p-Laplace equation with control and state constraints. The coefficient of the p-Laplacian, the weight u, we take as a control in L1(Ω). We discuss a relaxation of such problem following the so-called Henig regularization scheme.